PEMANFAATAN TEPUNG PACI-PACI (Leucas lavandulaefolia) UNTUK MENGOBATI INFEKSI Aeromonas hydrophila PADA IKAN PATIN (Pangasius sp.) - Menik Sri Rejeki; Ade Dwi Sasanti; Ferdinand Hukama Taqwa (Universitas Sriwijaya, 2018)
ABSTRACTMotile Aeromonas Septicaemia (MAS) is one of bacterial A. hydrophila disease frequently infecting freshwater fish include catfish (Pangasius sp.). Controling the disease of bacterial use chemical antibiotic will cause environment pollution. The aim of this research was to determine utilization of natural material that contain antibacterial such Leucas lavandulaefolia powder as antibacterial to treat of A. hydrophila infection for catfish. The implementation of research was from September until October 2014 at the Laboratorium Budidaya Perairan, Faculty of Agriculture, Sriwijaya University and Laboratorium UPT Klinik Kesehatan Sriwijaya University. Research method was using Completely Randomized Design (CRD) with five treat and three replications. The catfish was infected by A. hydrophila with clinical feature were (inflamed and hemorrhage) that give addition Leucas lavandulaefolia powder on commercial feed as many as 4%, 6%, 8%, and 10%. The result showed that addition 10 % of Leucas lavandulaefolia powder on commercial feed was the best to treat of A. hydrophila infection for catfish were significant (P<0,05). In vitro test result showed that Leucas lavandulaefolia powder at a concentration 10% as an antibacterial potential of A.hydrophila with inhibitor zone diameter 0.5 cm, at in vivo test the catfish that gives addition Leucas lavandulaefolia powder on commercial pellet as many as 10% capable hematocrit increase, reducing leucocyte completely, produce recovery percentage 84.44%, the survival rate 76.67%, highest absolute growth of catfish 3.03 g and higest absolute length of catfish 0.89 cm. Keywords : A. hydrophila, catfish, Leucas lavandulaefolia powder